Hubungan Media Sosial Instagram dengan Minat Konsumen Menggunakan Jasa Hair Stylist Mahasiswa - Zaeny, Lia Laelliyah; Armandari, Mari Okatini; Ambarwati, Neneng Siti Silfi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the relationship between Instagram social media usage and consumer interest in hairstylist services from students at Jakarta State University. The background of this research is based on the increasing development of information technology, particularly the use of social media as an effective digital promotional tool. The method used was a quantitative approach with a correlational survey technique. The sample in this study consisted of 100 respondents who were active followers of Instagram accounts of students providing hairdressing services, selected through purposive sampling. The research instrument was an online questionnaire with a Likert scale that included indicators of context, connection, communication, and collaboration for the Instagram variable, and indicators of interest, income, access, and qualifications for the consumer interest variable.The results of the Pearson product-moment correlation test showed a very strong relationship between Instagram usage and consumer interest, with a correlation coefficient of 0.816. This demonstrates that the more optimal the use of Instagram social media, the higher the consumer interest in student hairstylist services. Context and communication indicators were the dominant aspects that shaped interest, through the presentation of attractive portfolios and direct interactions such as direct messages and comments. This study emphasizes the importance of digital content and communication strategies in attracting market interest, particularly in the beauty services industry